Technology-Enabled Language Leaning: Mediating Role of Collaborative Learning - Divya Jyot Kaur; Niraja Saraswat; Irum Alvi (National Research University Higher School of Economics, 2023)
Background. Technology-Enabled Language learning (TELL) encourages peer communication and collaboration through its innovative instructional methods. Collaborative student activities are recognised as an important component of the instructional approach of higher education, More recently, collaborative learning in conjunction with digital teaching tools has emerged as a preferred SLA pedagogical approach. Despite growing interest in TELL, research into the effects of collaborative learning on affective factors in SLA remains unexplored. Purpose. The aim of the proposed study is to identify factors influencing the behavioral intention of students to use WhatsApp for second language acquisition. Constructs from previous models: performance expectancy, effort expectancy, and perceived relevance (UTAUT) are tested, along with the mediating role of a new variable 'collaborative learning'. Methods. Using the convenience sampling technique, the sample comprises 202 undergraduates studying in Institutes in Rajasthan, India. Data collected through Google forms was analyzed through IBM SPSS ver. 26 and Smart-PLS ver. 3.2.9, using structural equation modeling. Results. A positive and significant relationship was established between all the selected constructs. The indirect effects were positive, yet less significant than the direct effects. Moreover, the partially mediating effect of collaborating learning was affirmed. Empirical data confirms that collaborative learning acts as a mediating variable enhancing the intention to use WhatsApp for SLA. Conclusion. The present study makes an original and innovative contribution to language studies by analysing the relationship between the predictors. Such a systematic understanding of the topic can assist instructors in designing robust future pedagogical techniques.